Two new species in the genus Kolla Distant (Hemiptera: Cicadellidae: Cicadellinae) from China, with DNA barcoding data - Feng, Ling; Zhang, Yalin (Zootaxa, 2017)
Two new species of the genus Kolla from China, K. medsimilis and K. brevis spp. nov., are described and illustrated. Sequence data for the barcoding region of mitochondrial gene COI for these two new species were obtained and deposited in GenBank.